1972
DOI: 10.2105/ajph.62.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological aspects of gallbladder and biliary tract neoplasm.

Abstract: All newly diagnosed cases of gallbladder cancer in Israel over a six-year period were reviewed. Incidence findings are reported with respect to sex, and the distribution among females born in Europe, Asia, and Africa. The findings presented seem to suggest an etiological role for cholelithiasis in gallbladder cancer, but the authors emphasize the need for substantiation by prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1973
1973
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…Other study from India (Pandey et al, 2001) reported presence of gall stones in 70% gallbladder cancer patients. In a study (Hart et al, 1972) from United States, it was found that 74% females and 26.7% males had a previous history of gallstone disease, while on pathological examination of resected specimens gallstones were found in 69% males and 83% females, suggesting a high incidence of silent gallstones among male carcinoma patients. Another study (Black et al, 1977) found gallstones in 41 out of 56 patients of southwestern American Indian origin, an incidence of 73.2%.…”
Section: Discussionmentioning
confidence: 96%
“…Other study from India (Pandey et al, 2001) reported presence of gall stones in 70% gallbladder cancer patients. In a study (Hart et al, 1972) from United States, it was found that 74% females and 26.7% males had a previous history of gallstone disease, while on pathological examination of resected specimens gallstones were found in 69% males and 83% females, suggesting a high incidence of silent gallstones among male carcinoma patients. Another study (Black et al, 1977) found gallstones in 41 out of 56 patients of southwestern American Indian origin, an incidence of 73.2%.…”
Section: Discussionmentioning
confidence: 96%
“…Three-fourths of patients with carcinoma of the gallbladder have cholelithiasis [ 1,3]. Multivariate analysis has shown that the presence of gallstones is a risk factor independent of age or sex [4]. The size of the calculi was found to correlate with the probability of gallbladder carcinoma [5].…”
Section: Etiology and Epidemiologymentioning
confidence: 99%
“…GBC is a highly fatal disease with poor prognosis. For lesions confined to the gallbladder mucosa, the 5-year survival rate is about 32% and in more advanced stages 1-year survival rate is just 10% [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%